Feminist Legal Theory on the Criminalization of Abortion for Rape Victims - Irda Nur Khumaeroh; M. Rizal Bagaskoro (Law Development Journal, 2026)
In Indonesia, abortion is a complicated issue, caught between criminal charges, intense social stigma, and a health information system that's frustratingly murky and hard to navigate. Legally, the government only allows it in very specific cases: dire medical emergencies or pregnancies stemming from rape. This paper leans on Feminist Legal Theory to unpack all this—a framework that calls out how traditional law feels stamped with "masculine" traits, all cool-headed rationality, objectivity, abstract logic that often brushes aside what women actually go through. This study focuses on how the rules handle abortion for rape survivors and why it still gets hit with criminal labels, viewed squarely through that feminist legal lens. Using a normative juridical approach, literature and secondary data are analysed through both statutory and historical angles. The findings show that abortion for women rape victims in Indonesia is legally considered as acts punishable with criminal penalties. In the previous version of KUHP, abortion was regulated in Articles 299, 346, 347, 348, and 349. Amendment of these provisions then regulate legal abortion procedures through Law Number 1 of 2023 concerning the Criminal Code, Law Number 17 of 2023 concerning Health, and Government Regulation Number 61 of 2014. When abortion criminalization is analysed using feminist legal theory, particularly the radical feminism stream, the law still has not made women have equal legal protection. Criminalization of abortion against women can be analysed through the perspective of radical feminist theory encompassing: control over women's bodies, punishment of women's independence, stigma and misinformation, socio-economic inequality, dehumanization of women.